Effect of administration of leptin on thyroid hormone in oxidative stress induced rats - Rabeea Madhkhoor1Shaymaa; Raisan Ibrahim2Ihsan (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this study was to investigate the relationship between exogenous leptin and thyroxin on some stress types in rats. In this study 60 male wistar albino rats were divided into two main groups (first was 5 day, and second was 10 day), each one subdivided into six groups (5 rat per subgroup): Control And five treated groups ,which include: Leptin (10 Î¼g/kg leptin, sc. daily), oxidative stress (0.5% H2O2), leptin+ oxidative stress, Diabetes, (induced by single injection of streptoztocin (65 mg/kg bw)), and Leptin + diabetes. At the end of the experiments the blood collected by cardiac puncture under anesthesia. Plasma thyroxin and corticosterone were measured. Our results showed that stress decreases thyroxin level and increases corticosterone level, while leptin treatment reverse these changes.